2006
DOI: 10.2514/1.19528
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Conical Axial Injector on Hybrid Rocket Performance

Abstract: This paper analyzes the results obtained from a series of static firings of a lab-scaled hybrid rocket in which gaseous oxygen was supplied into axial-symmetric polyethylene cylindrical grains through two different injector configurations: an axial conical subsonic nozzle and a radial injector. The axial injector is interesting because of its relatively easy design, the higher regression rates, and the noticeably stable motor operation. To exploit its qualities, not only the assessment of the regression rate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 23 publications
5
61
0
3
Order By: Relevance
“…The large fluctuation in the initial 2 s is due to the start-up unsteadiness and should be ignored. 7) After this period to 4 s, the nozzle throat area is nearly constant, showing that the nozzle throat erosion started 4 s after the startup. This result agrees with Fig.…”
Section: Data Reduction Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The large fluctuation in the initial 2 s is due to the start-up unsteadiness and should be ignored. 7) After this period to 4 s, the nozzle throat area is nearly constant, showing that the nozzle throat erosion started 4 s after the startup. This result agrees with Fig.…”
Section: Data Reduction Methodsmentioning
confidence: 93%
“…Carmicino et al showed experimentally that the efficiency η is almost constant during firing except for the initial and final transients unless the flow field structure greatly changes. 7) Figure 12 shows histories of η with and without considering nozzle throat erosion by gray and black solid lines, respectively. The efficiency η without considering the nozzle erosion begins decreasing at 4 s. On other hand, the history with considering the nozzle erosion is more reasonable, being almost constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theoretical and experimental studies have shown that the fuel regression rate in a hybrid motor is highly dependent on the mass ux passing through the fuel port [21][22][23]. Thus, in most studies, the regression rate only correlates with a parameter given by: _ r = a G n o : (9) For a xed amount of fuel and oxidizer, it has been reported that the fuel regression weakly depends on the pressure of the combustion chamber, longitudinal distance from the edge of the fuel, and port diameter of the fuel [24][25].…”
Section: Regression Rate Correlationmentioning
confidence: 99%
“…NTRT builds from the governing equations and concepts of the reconstruction techniques introduced in Ref. [9][10][11] to reconstruct the nozzle throat radius R t and ξ histories through data reduction of commonly measured experimental values: (1) oxidizer mass flowrate, ox m  ; (2) (aft) chamber pressure, P c ; (3) thrust, F ; (4) overall fuel mass consumed, M f ; and either (5a) final nozzle throat radius, R t,f ; or (5b) nozzle exit pressure, P e , in the case that R t,f is not obtainable.…”
Section: Introductionmentioning
confidence: 99%